Peranan Ahli Forensik Dalam Pembuktian Penyebab Kematian Remaja Putri Di Kuburan Cina Palembang - Witasya Aurelia Sulaeman; Handar Subhandi Bakhtiar (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
When it comes to crime, evidence is an issue that plays an important role in the legal process. This evidence determines the fate of the accused. In the event that the results of the examination of evidence based on the evidence provided by law are not sufficient to prove the guilt of the accused, if the guilt of the accused can be proven based on evidence, the accused is acquitted. According to Article 184 of the Criminal Procedure Code, a defendant must be punished first before being sentenced. Expert testimony is valid evidence, and Visum et Repertum can also be used as evidence to replace a manuscript in the form of a letter because Visum et Repertum is one aspect of the role of experts and/or expert testimony, so the relationship between the two cannot be separated. This study aims to determine the role of forensic legal experts in proving the cause of death and the position of evidence to reveal the cause of death of the victim. The method used in this study is normative legal research, using a statute approach and a case approach. The results of this study indicate that the role of forensic legal experts and the regulation of criminal law based on the evidentiary power of the visum et repertum in proving the cause of the victim's death.